2016
DOI: 10.1039/c6cp00493h
|View full text |Cite
|
Sign up to set email alerts
|

Surface-active ionic liquids in micellar catalysis: impact of anion selection on reaction rates in nucleophilic substitutions

Abstract: A series of surface-active ionic liquids based on the 1-dodecyl-3-methylimidazolium cation and different anions was synthesized and applied for micellar catalysis of nucleophilic substitutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 63 publications
(109 reference statements)
0
51
0
Order By: Relevance
“…12,13 More recently, the properties of catanionic ionic liquids, containing both anions and cations with hydrophobic tails, have proved to be exceptional. 14,15 Surface-active ionic liquids have already been well explored for a number of applications in synthesis, 16,17 catalysis 18,19 and separations 20,21 rendering them ideally suited for the development of targeted microemulsions, 22−26 and for their separation. 27 …”
Section: Introductionmentioning
confidence: 99%
“…12,13 More recently, the properties of catanionic ionic liquids, containing both anions and cations with hydrophobic tails, have proved to be exceptional. 14,15 Surface-active ionic liquids have already been well explored for a number of applications in synthesis, 16,17 catalysis 18,19 and separations 20,21 rendering them ideally suited for the development of targeted microemulsions, 22−26 and for their separation. 27 …”
Section: Introductionmentioning
confidence: 99%
“…Table also exhibited the CMC values concerning to 1‐methyl, 3‐octyl/3‐dodecylimidazolium trifluoroacetate and 1‐methyl, 3‐dodecylimidazolium methanesulfonate (Cognini et al, ; Šarac et al, ; Wang et al, ). Comparing these values with the corresponding 1‐alkylimidazolium derivatives, it can be observed that these last SAIL display lower CMC values.…”
Section: Resultsmentioning
confidence: 99%
“…Both cationic and anionic SAIL have been designed and investigated for their self‐assembly by changing the alkyl chain length, charged head group structure, functional groups, and counterions (Anouti et al, ; Baker et al, ; Blesic et al, , ; Galgano and El Seoud, ; García et al, ; Pillai et al, ; Rao et al, ; Šarac et al, ; Singh et al, ; Wang et al, ; Wang and Wang, ). The high tunability of IL opens up a broad range of applications for SAIL such as in micellar catalysis (Adam et al, ; Bica et al, ; Cognini et al, ) and in analytical chemistry and separation science (de Faria et al, ; Pino et al, ; Ressman et al, ). It was also demonstrated that some SAIL can be effective alternatives to the surfactants commonly used in enhanced oil recovery (EOR) processes with important advantages over the traditional surfactants and polymer‐flooding methods (Bera and Belhaj, ; Lago et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several applications of ionic liquids (ILs) as micellar catalysts have been developed [23][24][25][26]. However, their application as micellar epoxidation catalyst has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%